2015
DOI: 10.1016/j.ypmed.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-component camp-based intervention on inflammatory markers and adipokines in children: A randomized controlled trial

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Huang, T., Larsen, K. T., Møller, N. C., Ried-Larsen, M., Frandsen, U., Andersen, L. B. (2015 Methods:One hundred and fifteen children were recruited in Odense, Denmark (2011Denmark ( -2014. The participants were randomly allocated to either the day camp intervention arm (DCIA) or the standard intervention arm (SIA). The intervention for the DCIA comprised a 6-week camp intervention and a 46-week family-based intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…Our results are in line with previous studies, such as the HELENA study and studies from other groups, 23,40–44 which have also shown that obesity related inflammation may occur long before the onset of puberty. The fact that some of the observed associations were strongest in prepubertal children underlines and confirms the importance of identifying children at risk and initiating therapy as early as possible.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous studies, such as the HELENA study and studies from other groups, 23,40–44 which have also shown that obesity related inflammation may occur long before the onset of puberty. The fact that some of the observed associations were strongest in prepubertal children underlines and confirms the importance of identifying children at risk and initiating therapy as early as possible.…”
Section: Discussionsupporting
confidence: 93%
“…Contrarily, a 12-week exercise intervention study with lean adolescents males found an increase in adiponectin, IL-6 and CRP, although none of these changes were associated with variations in body fat composition [110]. Similar results were found in other studies [111].…”
Section: Interventional Studies and Adiponectin Levelssupporting
confidence: 77%
“…One study was a non-randomised trial (Halberstadt 2017);Seven studies did not report the disaggregated data for children with obesity or overweight (Donnelly 2009; Donnelly 2013; Gentile 2009; Hillman 2014; Murray 2008; Puder 2011; Reed 2010);Two studies employed lifestyle interventions without the intention to prevent or reduce obesity (Crova 2014; Pesce 2016b);Eight studies used non-eligible tools to assess school or cognitive outcomes (e.g. self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies did not report the disaggregated data for children with obesity or overweight (Donnelly 2009; Donnelly 2013; Gentile 2009; Hillman 2014; Murray 2008; Puder 2011; Reed 2010);…”
Section: Resultsmentioning
confidence: 99%